Biliary glutathione promotes the mucosal metabolism of luminal peroxidized lipids by rat small intestine in vivo. - Aw, T Y (1994)
We previously found that exogenous GSH enhances mucosal GSH and promotes lipid hydroperoxide metabolism by rat small intestine (AW, T. Y., and M. W. WIlliams, 1992. Am. J. Physiol. 263:G665-G672). In this study, we have developed an in vivo bile and lymph fistula rat model to test the hypothesis that biliary GSH is an important luminal source of GSH. Peroxidized fish oil was infused into the proximal intestine, and hydroperoxide accumulation in lumen, mucosa, and lymph was determined. Diversion of bile decreased mucosal GSH and increased hydroperoxide accumulation in all fractions. Supplementation with GSH, but not with GSSG, increased tissue GSH and attenuated hydroperoxide accumulation (50-60%), consistent with enhancement of hydroperoxide removal by exogenous GSH. Addition of native bile deficient in GSH, but not cysteine, cystine, or GSSG, decreased luminal and lymph hydroperoxide levels by 20-30%. Amino acid supplementation concurrently attenuated hydroperoxide recoveries in these fractions by 30-40% and increased mucosal GSH by 40%, indicating a role for biliary amino acids in hydroperoxide elimination. The effect of amino acids was abolished by buthionine sulfoximine, confirming their role in GSH biosynthesis. Collectively, the results demonstrate that bile is a rich source of reductant for maintaining mucosal GSH to promote intestinal metabolism of luminal peroxidized lipids.